EDUKASI BAHAYA GADGET DAN FESTIVAL KEBAIKAN: WUJUD PENGABDIAN UKM PRO.ASTA UNIVERSITAS BATTUTA - Ruziq, Fahmi; Wayahdi, M. Rhifky; Nanda Ginting, Subhan Hafiz; Wahyuni, Dewi; Sridewi, Nurmala (Smart Education, 2025)
Abstract: The development of digital technology brings both conveniences and challenges for children. Excessive gadget use can negatively impact children’s physical, psychological, and social well-being. The community service programme